PENINGKATAN PENGETAHUAN LANSIA DIABETES MELITUS TENTANG MENU HARIAN DAN PRINSIP 3J MELALUI MEDIA DIABETV CARE BOX SEBAGAI UPAYA PENGENDALIAN GLIKEMIK - Iis Sulastri (Poltekkes Kemenkes Riau, 2026)
Diabetes Mellitus (DM) is a degenerative disease that requires continuous nutritional managementthrough the 3J diet principles (Schedule, Amount, and Type). This community service aims to increase the knowledge of elderly patients with DM in the Pringsewu Community Health Center work area through innovative educational media intervention. The participants were 29 elderly women aged 41-60 years. The method involved providing interactive education using the